Effects of correlated color temperature of light on thermal comfort, thermophysiology and cognitive performance. (1st March 2023) - Luo, Wei; Kramer, Rick; Kompier, Maaike; Smolders, Karin; de Kort, Yvonne; van Marken Lichtenbelt, Wouter
Abstract: Anecdotal evidence suggests that the correlated color temperature (CCT) of light can affect thermal comfort. Previous literature mostly investigated this effect over a short duration (<1 h) and often attributed it to the hue-heat hypothesis (color-temperature association), which posits that the visual experience of blue colors (high CCT) results in a cooler temperature sensation than red/yellow colors (low CCT) do. However, with longer duration, non-visual effects of CCT that elicit physiological changes may be at play additionally. Therefore, we contrasted two CCTs with relatively long exposures (>2 h; 2700 K vs. 5700 K with 500 lux illuminance at the eye) in office-like settings during mild cold exposure (17 °C) using a within-subject design (N = 16). The results indicate that CCT did not significantly affect thermal sensation in mild cold, which may be explained by the large interindividual variation in the color-temperature association. Interestingly, 5700 K even improved thermal comfort, decreased perceived shivering, and, after 1-h exposure, increased energy expenditure. Moreover, visual comfort was not significantly moderated by CCT, but 5700 K improved comprehensive cognitive performance. Concurrently, arousal and alertness were higher in 5700 K, potentially indicating greater non-visual effects in 5700 K. Further analysis revealed that thermal comfort significantly correlated with perceived shivering and visual comfort, but not with the color sensation of the light. Together, the results provide no support for the hue-heat hypothesis under mildly cold conditions and suggest that high CCT enhanced thermal comfort, alertness, arousal, and cognitive performance, likely via non-visual mechanisms that built up over longer exposure durations. Highlights: Effects of correlated color temperature (CCT) were tested with prolonged durations. Both visual and non-visual mechanisms of CCT may affect thermal comfort. The color-temperature (hue-heat) association has large interindividual variations. High CCT improves thermal comfort, alertness and performance in cold conditions.